Effect of water saturation on strength and deformability of building calcarenite stones: Correlations with their physical properties. (30th January 2020) - Rabat, Á.; Cano, M.; Tomás, R.
Highlights: Water saturation causes reductions of mechanical properties for calcarenites. Relationships between physical and mechanical properties. Correlations between UCS, Est and Is(50) in dry and saturated conditions. Abstract: Stone construction elements are frequently in moist environments or in direct contact with water. Design and test standards have traditionally ignored the water impact on rock materials. However, several studies have shown that moisture can cause drastic strength reductions and deformability increase in some sedimentary rocks. For that reason, the main objectives of this work are: a) to quantify and understand the influence of water saturation on strength and deformability of four porous calcarenite building stones widely used in SE Spain; b) to establish correlations between physical and mechanical properties of these rock materials in dry and saturated states and c) to compare the results with previous findings. The results showed a very significant reduction of mechanical properties such as unconfined compressive strength, Young's modulus and point load strength index when these stones undergo saturated. In addition, significant correlations between physical properties (density, porosity, P wave velocity and dynamic elastic parameters) and the mentioned mechanical properties were established in dry and saturated conditions. Additionally, relationships among the mechanical properties of stones in both states are also proposed.